An easy method to generate recombinant pseudorabies virus expressing the capsid protein of Porcine circovirus type 2d - Ren, Jingqiang; Madera, Rachel; Cunningham, Chase; Shi, Jishu; Wang, Lihua (Frontiers in Microbiology, 2023)
Homologous recombination is an effective way to generate recombinant viruses for vaccine research such as pseudorabies virus (PRV) and adenovirus. Its efficiency can be affected by the integrity of viral genome and the linearization sites. Here, we described a simple approach to isolate high degree of genome integrity for large DNA viruses and a time-saving method to generate recombinant PRVs. Several cleavage sites in the PRV genome were investigated by using the EGFP as a reporter gene for identification of PRV recombination. Our study showed that cleavage sites of XbaI and AvrII are ideal for PRV recombination which showed higher recombinant efficiency than others. The recombinant PRV-EGFP virus can be easily plaque purified in one to two weeks after the transfection. By using PRV-EGFP virus as the template and XbaI as the linearizing enzyme, we successfully constructed the PRV-PCV2d_ORF2 recombiant virus within a short period by simply transfect the linearized PRV-EGFP genome and PCV2d_ORF2 donor vector into BHK-21 cells. This easy and efficient method for producing recombinant PRV might be adapted in other DNA viruses for generation of recombinant viruses.